A MODEL OF PARTICIPATORY LOCAL DEVELOPMENT OF THE CITIZEN SECTORS IN THE LOCAL ORGANIZATION IN PHITSANULOK - Dontumpai, Phattanaphakorn; Bodeerat, Chot; Taomiitr, Sornchai (Journal of Social Science and Cultural, 2023)
The objective of this research is 1) Study the level of participation in development Local areas of public sector in local government organization area Phitsanulok Province. 2) Study factors affecting participation in local development of the public sector in local government organization area Phitsanulok Province. 3) Propose guidelines for participation in the local development of public sector in local government organizations area Phitsanulok Province. The sample group of 400 people and target group of key informants of 27 people. The results of the quantitative research found that. When separated into each area, it was found that participation was at a high level 3 aspects include. Participation in selecting individuals as representatives at the local level. Participation in voting to elect representatives at the local level. And participation in following local political information. Participation is at a low level in 2 aspects. Participation in monitoring and inspecting the project. And participation in examining the 3-year development plan. Qualitative research results found that factors affecting participation in local development of the public sector in Local government organization area Phitsanulok Province consist of 5 aspects: 1) Participation in following political information at the local level is alert and accessible. Information is easy. 2) Participation in community work regarding solving problems at the local level is difficult. Complicated and unnecessary. 3) In terms of participation in selecting people to be local level representatives. They are alert and interested in politics local level. 4) In terms of participation in the preparation of local development plans. It was found that it was through brainstorming in a narrow circle. 5) Participation in monitoring local development plans. Is considered an important tool for development.